Comparing the hand grip power and creatine kinase levels of U-17 judo national team athletes before and after a 6-week strength training - Celik, N. M.; Soyal, M. (Pedagogy of Physical Culture and Sports, 2020)
Purpose: The aim of this study is to compare the hand grip power and creatine kinase levels of male and female U-17 National Team Athletes before and after a 6-week strength training. Material: 15 female and 15 male U-17 athletes, who previously participated in international competitions, participated in our study. Besides the hand grip power and creatine kinase values, age, height, weight, and BMI (body mass index) values of the athletes were measured before and after the training. As the conclusion of the measurements, the mean age of the female participant athletes was determined as 14,93 years, their mean height was 158,3 cm, and the mean age of the male athletes was 15,73 years, while their mean height was 173,1 cm. Results: As the conclusion of the measurements, it was determined that there were statistically significant differences between the right hand grip power and left hand grip power parameters of male and female participant athletes measured before and after the 6-week training. Moreover, it was determined that there were statistically significant differences between the pre-test and post-test measurements of creatine kinase values of both male and female athletes (p> 0,05). Conclusions: As the conclusion, it was determined that the 6-week strength trainings applied to U-17 Judo National Team athletes caused significant changes in their hand grip power and creatine kinase values. The significant results obtained from our study are considered to be originated from the duration, scope, frequency, severity, and content of the training.